Short Communication: Two new species and new record of Psydrax Gaertn. (Rubiaceae: Vanguerieae) in Borneo - RIDHA MAHYUNI; TATIK CHIKMAWATI; NUNIK SRI ARIYANTI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mahyuni R, Chikmawati T, Ariyanti NS. 2019. Short Communication: Two new species and new record of  Psydrax Gaertn. (Rubiaceae: Vanguerieae) in Borneo. Biodiversitas 20: 2011-2015. Psydrax sabahensis Mahyuni and P. wongii Mahyuni are two new species endemic to Borneo proposed in this present study with descriptions, illustrations and map of distribution provided. Psydrax sabahensis has blades ovate to elliptic, with angle 60º to the midrib, tertiary venation conspicuous on both side, petiole length 10-13 mm long, inflorescence sub-umbellate and pedicels 23-27 mm long. Psydrax wongii has blade elliptic, with angle 45º to midrib, apex acuminate to caudate, secondary veins 3-4 pairs, tertiary venation inconspicuous on upper side and slightly wrinkled on lower surface. The presence of P. maingayi (Hook.f.) Bridson in Borneo, previously thought to be a Malay Peninsula endemic species, is also confirmed as a new record.